Making Skin Visible: How Consumer Culture Imagery Commodifies Identity. (June 2018) - Borgerson, Janet L; Schroeder, Jonathan E
Human skin, photography, and consumer culture combine to produce striking images designed to promote visions of the good life. Branding and marketing imagery mobilize skin to resonate and communicate with consumers, which influences the meaning-making possibilities of skin more broadly. Representations of skin in consumer culture, including marketing communications, are anything but 'blank' backgrounds or 'neutral' meaning spaces. We analyse how skin 'appears' to work, and how its appearance in consumer culture imagery reveals ideological and pedagogical aspects of skin. Building upon psychodynamic and interdisciplinary understandings of skin, we discuss dimensions of the body that feed marketing communications and branding. We highlight representational fetishization and the epidermal schema as conceptual tools to interrogate the commodification of skin and as constitutive elements in processes of skin commodification. We provide theoretical insights to address the ways in which skin is implicated in new and emerging concerns of digital representational practices.